Risk and Supply Chain Mitigation Analysis Using House of Risk Method and Analytical Network Process - Shelvy Kurniawan; Denny Marzuky; Rio Ryanto; Vanny Agustine (Bina Nusantara University, 2021)
The research studied PT XYZ, a company engaged in the palm oil industry which has eleven subsidiaries spread across five provinces in Indonesia. The research focused on analyzing supply chain risks in PT A, a subsidiary of PT XYZ. The objective was to find out and reduce unexpected costs that the company may experience caused by the risks in supply chain. Furthermore, the aim was to determine priority of risk agents and risk mitigation actions. The research method was a mixed methods, which combined both qualitative and quantitative analysis to answer the research questions. Data analysis procedure involved Supply Chain Operations Reference (SCOR), House of Risk (HOR) 1, and Analytic Network Process (ANP). The SCOR method was used for mapping supply chain activities, the HOR 1 was to determine the priority of the risk agent, and the ANP was to determine the priority of mitigation actions. The results show that there are 36 risk events and 35 risk agents. 19 risk agents are categorized as priority risks and 11 preventive actions are proposed to be implemented by PT XYZ. The research suggests that the company implement mitigation actions according to priority in accordance with the research results.